(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article authors explored the reasons of crime happening, mechanism of criminal actions, the beginning and develop of crime, also they presented an analysis and characterful solutions of problems by depiction of statistical information. In addition to the all things there are unique solutions to that cases which were characterized by detailed classification of crime in combination with actual dissection of its causes and ways of resolution. Key words: crime politics, insurance from crime, economical crimes, principle of commonwealth in crime struggle, basic facet of crime politics.